1990
DOI: 10.1002/jor.1100080110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maturation and aging on the structure and content of link proteins in rabbit articular cartilage

Abstract: We have examined extracts of articular cartilage from rabbits aged 3-100 weeks for evidence of age-related changes in the structure and content of link protein (LP) in this tissue, with the following findings: (a) Two major molecular weight forms of LP were seen on SDS-PAGE (41 and 48 kDa) and the proportion of these changed markedly with age. The 48 kDa species was predominant in young animals (representing about 78% of the total LP at 5 weeks) whereas the 41 kDa species increased in amount with age (represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…These characteristics are consistent with those reported in rat chondrosarcoma cell cultures stimulated with retinoic acid, where activity was detected in media using an artificial recombinant aggrecan interglobular domain protein substrate (22). In contrast to earlier studies (34), a recent publication demonstrated the ability of membranes isolated from stimulated chondrocytes to generate aggrecan fragments formed by cleavage at the Glu 373 -Ala 374 bond (36). This recent identification of aggrecanase activity associated with chondrocyte membranes, in addition to our demonstration of soluble activity in culture media, open the possibility that aggrecanase may be an integral membrane protein that is subsequently cleaved to a soluble form or that it may be a soluble enzyme that is associated with a cell surfacebinding protein on the chondrocyte membrane.…”
Section: Treatmentsupporting
confidence: 91%
See 1 more Smart Citation
“…These characteristics are consistent with those reported in rat chondrosarcoma cell cultures stimulated with retinoic acid, where activity was detected in media using an artificial recombinant aggrecan interglobular domain protein substrate (22). In contrast to earlier studies (34), a recent publication demonstrated the ability of membranes isolated from stimulated chondrocytes to generate aggrecan fragments formed by cleavage at the Glu 373 -Ala 374 bond (36). This recent identification of aggrecanase activity associated with chondrocyte membranes, in addition to our demonstration of soluble activity in culture media, open the possibility that aggrecanase may be an integral membrane protein that is subsequently cleaved to a soluble form or that it may be a soluble enzyme that is associated with a cell surfacebinding protein on the chondrocyte membrane.…”
Section: Treatmentsupporting
confidence: 91%
“…However, aggrecanase activity as measured by cleavage of exogenous aggrecan was not detected in media from these cultures (34). We had previously found that induction of MMP-3 in cartilage cultures by IL-1 resulted in the elution of only the inactive zymogen into the culture media at early time points, although both the zymogen and active forms of the enzyme were present within the matrix (35).…”
Section: Treatmentmentioning
confidence: 88%
“…The report by Flannery and Sandy [29] that MMP-13 is the predominant MMP expressed by chondrocytes under conditions of accelerated matrix resorption, raises important questions about the role of MMP-13 in normal and pathological aggrecan catabolism. Recent data has shown that in addition to the predominant involvement of aggrecanase [18,19,35], there is also a significant involvement of one or more MMPs in aggrecan degradation.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-13 exhibits 86% homology in amino acid sequence to rat and mouse MMP-1 [27,28] suggesting that rodent collagenase and human MMP-13 represent a gene product that is distinct from MMP-1 [28]. MMP-13 is also the major MMP expressed by retinoatestimulated chondrocyte monolayers [29]. Because of its potential role in aggrecan degradation it was of interest to examine the specificity of this new MMP for an aggrecan substrate.…”
Section: *Corresponding Author Fax: (61) (3) 9345 6668mentioning
confidence: 99%
“…However, these studies have been unsuccessful in defining any specific agent responsible for the degradation of aggrecan (18). Nonetheless, experimental data using purified aggrecan and modified aggrecan as a substrate for testing purified enzyme preparations in vitro have yielded some information on the specific cleavage sites of the enzymes themselves, but this work has not directly helped in determining the identity or biochemical properties of aggrecanase (14,19,20).…”
mentioning
confidence: 99%